Dato' Zawiah Baba / Nor Adilah Mohd Noor Aimi and Khuzairiah Shaari - Mohd Noor Aimi, Nor Adilah; Shaari, Khuzairiah (2011)
Dato' Zawiah Baba is one of the women that were successful in their career. She ever holds as an assistant of language at Dewan Bahasa dan Pustaka impermanent waiting their examination result at University Malaya, Director -General, National Library of Malaysia from 1st December 2001 to 20th January 2005 and current designation is Principle Research Fellow, Institute of the Malay World and Civilization, (ATMA), National University of Malaysia from 14 September 2007. Many contributions had been by Dato' Zawiah Baba in order to make people in Malaysia like to reading. Amongst her contribution that make big impact to people is Reading Campaign in 2002. She does that activities as answer to government exclamation cause of their responsibility to provide information and services to people who need it. In 1984 she was a Vice President of Library Association and was ask to attent conference in Indian that was the 50th Golden Anniversary of the Indian Library Association. At that time she was the only senior librarian from Malaysia that joins that conference.